Effects of dense-planting pattern of apple on soil moisture in Weibei dry plateau - BAI Gangshuan; ZOU Chaoyu; DU Sheni (浙江大学学报. 农业与生命科学版, 2020)
In order to reduce the adverse effects of soil desiccation on apple production and provide scientific support for apple cultivation in Weibei dry plateau, taking apple orchard with vigorous stock dense-planting in full bearing age as a control, the soil moisture contents of dwarfing stock and semi-dwarfing stock dense-planting orchards with same tree age and same fruit yields were adjusted to the same level in the 0-300 cm soil layer before germination stage, and the soil moisture contents in different soil layers in different orchards were monitored regularly. The result showed that the soil moisture content in the 0-300 cm soil layer in the dwarfing stock dense-planting orchard was higher than that in the semi-dwarfing stock dense-planting orchard, and that of in the semi-dwarfing stock dense-planting orchard was higher than that in the vigorous stock dense-planting orchard, and the gap between different orchards gradually increased from spring to autumn. The soil evapotranspiration of the dwarfing stock dense-planting, semi-dwarfing stock dense-planting and vigorous stock dense-planting orchards were 4.51, 46.37 and 92.70 mm higher than that of the precipitation in the same period during the monitoring period (from March to November in 2016), respectively; as such, they were －18.06, 22.35 and 65.34 mm higher during the growth period of apple trees (from April to October in 2016), respectively, which indicated that the vigorous stock dense-planting pattern increased the soil desiccation. The water use efficiency of dwarfing stock dense-planting and semi-dwarfing stock dense-planting orchards increased by 14.98% and 9.58%, respectively. In a sum, dwarfing stock dense-planting and semi-dwarfing stock dense-planting patterns could not only slow down the soil desiccation, but also could increase soil water use efficiency and production value, so dwarfing and semi-dwarfing stock dense-planting patterns should be popularized in Weibei dry plateau.